IMPLEMENTASI PEMBANGUNAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Asep Hidayat (GoAcademica Research dan Publishing, 2022)
Community welfare is one of the goals of the Sustainable Development Goals (SDGs) and is a reflection of the success of development carried out by the government. In Indonesia, various policies or programs have been carried out by the government to overcome poverty in order to improve people's welfare. The handling of poverty needs to be understood as a world problem, so it must be handled globally as well. So that each poverty alleviation program must be understood as a whole and mutually interdependent with several other activity programs. The SDGs state no poverty as the first priority point. This means that the world has agreed to eliminate poverty in any form in all corners of the world, including Indonesia. This study aims to find out whether the existence of SDGs can help in community welfare. The research is descriptive qualitative with data collection techniques through literature studies. The results of the study can be concluded that welfare in Indonesia is still a problem, which is caused by poverty that has no end even though various solutions and policies issued by the government have been implemented but in practice the problem of poverty still occurs in Indonesia. In measuring welfare or measuring the quality of life, of course, it will involve elements of health, education, personal activities, and fulfilling their rights. All of these things can be fulfilled properly and quickly if the construction infrastructure is good and can be felt directly by the community.